The Effect of Internal Control System, Clarity of Budget Objectives and Delegation of Authority on Managerial Performance - Suhendra; Indri Septiani (PT Mattawang Mediatama Solution, 2023)
This study aims to determine and analyze the effect of the internal control system, budget target clarity and delegation of authority on government managerial performance This study uses primary data obtained from distributing questionnaires. The respondents in this study were several staff and employees at the Governor's office of South Sulawesi Province. The number of samples in this study were 64 respondents. Analysis of research data using multiple linear regression. The results showed that: (1) The internal control system has a positive and insignificant effect on government managerial performance. (2) Budget target clarity has a positive and insignificant effect on government managerial performance. (3) Delegation of authority has a positive and insignificant effect on government managerial performance.